Effects of serum irisin, neuregulin 4, and weight management on obese adolescent girls with polycystic ovary syndrome. Issue 9 (30th September 2021) - Cao, Shunshun; Hu, Yangyang
Abstract: The study is aimed at investigating the association of serum irisin, neuregulin 4 (NRG4), and anti-müllerian hormone (AMH) with adolescent obesity with polycystic ovary syndrome (PCOS) and the efficacy of weight management interventions. Serum levels of irisin, NRG4, AMH, sex steroid hormone, body mass index (BMI), serum insulin, and C-peptide were measured in 52 obese adolescent girls with PCOS (PCOS group) and 43 obese adolescent girls without PCOS (non-PCOS group). The levels of AMH, NRG4, serum irisin, sex steroid hormones, BMI, serum insulin, and C-peptide were evaluated in obese PCOS girls before and after one year weight management. The levels of AMH, serum insulin, NRG4, and total testosterone of PCOS group were significantly higher than those of non-PCOS group. On the contrary, serum irisin and serum C-peptide in PCOS group were significantly lower than that in non-PCOS group. The levels of fat mass, percent body fat, total testosterone, AMH, NRG4, and serum insulin in the obese girls with PCOS showed significant decreases compared with before weight management intervention. On the contrary, after one year of body weight management intervention, serum irisin and serum C-peptide was significantly increased. Adolescent obesity complicated with PCOS is significantly associated with glucose and lipid metabolism and sex steroid hormone disorders, but the exact pathophysiological and clinical features are highly variable. Weight management intervention can significantly improve the clinical symptoms and hematological indicators, serum irisin and NRG4 can be used as two essential biomarkers for evaluating weight management.